(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The SOPs must be validated prior to their use to prove their effectiveness in the environment of the respective blood bank. Realizing that the capacity to develop their own SOPs is currently limited in the countries of the South-East Asia Region, we have developed ’model’ SOPs for some of the essential procedures that are followed in blood banks. They are meant to serve as a reference and assist in writing and validating their own SOPs for all blood banks. We hope that these will not only serve as models for SOP growth, but will also enable blood transfusion services to use SOPs for different procedures and improve their quality systems.